FACTORS ASSOCIATED WITH ADHERENCE TO CERVICAL CANCER SCREENING AND EARLY DETECTION IN TASHKENT, UZBEKISTAN - Iskandarova Shakhnoza Tulkinovna,; Voitova Gavkhar Alisherovna, (The Bioscan, 2026)
This study evaluated factors associated with adherence to cervical cancer screening and its relationship with early detection among women attending consultation clinics in Tashkent, Uzbekistan. A retrospective cross-sectional review of medical records from January 2023 to December 2025 included 214 women aged 18–49 years. Screening within the recommended interval was documented in 160 women (74.8%), while 54 (25.2%) were non-adherent. Adherence was lowest among women aged 18–29 years (40.7%) and higher among those aged 30–39 years (87.1%) and 40–49 years (88.7%). Screening participation was significantly associated with marital status (OR 20.97; 95% CI 9.2–47.8), secondary or higher education (OR 10.0; 95% CI 4.9–20.5), employment (OR 5.89; 95% CI 2.9–11.9), and receipt of preventive counseling (OR 19.83; 95% CI 8.8–44.5) (p<0.001). Parity showed no significant association (p=0.49). Among screened women, abnormal cytology was identified in 34.4%, biopsy- confirmed cervical intraepithelial neoplasia in 25.6%, and early-stage lesions in 32.5%. Stage I invasive cancer was detected in 1.9% of screened participants. These findings highlight variations in screening adherence and early detection within the studied outpatient setting.